Pressure support-ventilation versus spontaneous breathing with "T-Tube" for interrupting the ventilation after cardiac operations - Lourenço,Isabela Scali (2013)
OBJECTIVE: To compare pressure-support ventilation with spontaneous breathing through a T-tube for interrupting invasive mechanical ventilation in patients undergoing cardiac surgery with cardiopulmonary bypass. METHODS: Adults of both genders were randomly allocated to 30 minutes of either pressure-support ventilation or spontaneous ventilation with "T-tube" before extubation. Manovacuometry, ventilometry and clinical evaluation were performed before the operation, immediately before and after extubation, 1h and 12h after extubation. RESULTS: Twenty-eight patients were studied. There were no deaths or pulmonary complications. The mean aortic clamping time in the pressure support ventilation group was 62 ± 35 minutes and 68 ± 36 minutes in the T-tube group (P=0.651). The mean cardiopulmonary bypass duration in the pressure-support ventilation group was 89 ± 44 minutes and 82 ± 42 minutes in the T-tube group (P=0.75). The mean Tobin index in the pressure support ventilation group was 51 ± 25 and 64.5 ± 23 in the T-tube group (P=0.153). The duration of intensive care unit stay for the pressure support ventilation group was 2.1 ± 0.36 days and 2.3 ± 0.61 days in the T-tube group (P=0.581). The atelectasis score in the T-tube group was 0.6 ± 0.8 and 0.5 ± 0.6 (P=0.979) in the pressure support ventilation group. The study groups did not differ significantly in manovacuometric and ventilometric parameters and hospital evolution. CONCLUSION: The two trial methods evaluated for interruption of mechanical ventilation did not affect the postoperative course of patients who underwent cardiac operations with cardiopulmonary bypass.